METODE PEMASARAN PISANG RAJA (Musa paradisiaca L) MENJADI OLAHAN NUGET MELALUI MEDIA ONLINE - Bambang Tri Kurnianto; Mufida Diah Lestari; Ermawati Dewi (FEBI UIN Sunan Gunung Djati Bandung, 2023)
This research refers to the development of nuget banana marketing methods through online media. The purpose of this research is to see how far online marketing methods can be used in the marketing process. The method used is a qualitative research method in order to get as much information as possible. This research was conducted in Tulungagung Regency because in several areas in Tulungagung there are lots of bananas and this is one of the products that can be processed into nuggets so that they have added value to the original product. The results of this study, the marketing of processed bananas into nuggets, has received a positive response from the community with many small entrepreneurs in Tulungagung Regency making processed banana products using online marketing methods through grab food and other (local) delivery services, and market places. From the development of this marketing method, it was able to boost the income of banana farmers because the selling value of these bananas experienced an increase in price.